Urine Assay for Tenofovir to Monitor Adherence in Real Time to TDF/FTC as PrEP - Koenig, Helen C. (HIV Med, 2017)
BACKGROUND: Tenofovir/Emtricitabine (TDF/FTC) is approved for pre-exposure prophylaxis (PrEP) against HIV infection. Adherence is critical for the success of PrEP but current adherence measurements are inadequate for real time adherence monitoring. We developed and validated a urine assay to measure tenofovir (TFV) to objectively monitor adherence to PrEP. METHODS: We developed a urine assay using high-performance liquid chromatography coupled to tandem mass spectrometry with high sensitivity/specificity for TFV that allowed us to determine TFV concentrations in log10 categories between 0–10,000 ng/mL. We validated the assay in 3 cohorts: 1) HIV-positive subjects with undetectable viral loads on a TDF/FTC-based regimen, 2) healthy subjects who received a single dose of TDF/FTC, 3) HIV-negative subjects receiving daily TDF/FTC as PrEP for 24 weeks. RESULTS: The urine assay detected TFV with greater sensitivity than plasma-based measures and with a window of measurements within 7 days from last tenofovir dose. Based on the urine log-linear clearance after last dose and its concordance with all detectable plasma levels, a urine TFV concentration > 1000 ng/mL was identified as highly predictive of presence of TFV in plasma >10 ng/mL. The urine assay was able to distinguish high or low adherence patterns within the last 48 hours (>1000 ng/mL vs. >10 to >100 ng/mL), as well as non-adherence (<10 ng/mL) extended over at least one week prior to measurement. CONCLUSIONS: We provide proof-of-concept that a semi-quantitative urine assay measuring levels of TFV could be further developed into a point of care test and be a useful tool to monitor adherence to PrEP.